Spatial Temporal Pattern of Urbanization in Far-West Province of Nepal - Panday, Tilak Raj (DMC Research Journal, 2024)
This study, titled Spatial Temporal Pattern of Urbanization in Far-West Province of Nepal aims to analyze the spatial and temporal trends of urbanization in the region, focusing on changes in urban population distribution and the factors driving these changes. Utilizing secondary data from the Central Bureau of Statistics of Nepal, covering the period from 1981 to 2021, the study employs tables, line graphs, and maps to illustrate urban growth patterns. The findings reveal a significant increase in the urban population from 71,108 in 1981 to 1,682,578 in 2021, with the number of urban centers rising from 2 to 34. The Terai region, particularly the districts of Kailali and Kanchanpur, shows the highest urbanization rates, while the Mountain and Hill regions have lower rates. The study concludes that rapid and uneven urbanization in the Far-west Province is driven by governmental policies and rural-to-urban migration, highlighting the need for effective urban planning and resource allocation to manage the associated challenges and opportunities.